ANALISIS FRASE ADVERBIA PADA MAJALAH NATIONAL GEOGRAPHIC - BILMONA, RIZQI NOVALIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â This research is entitled â€œAn Analysis of Adverbial Phrases on National Geographic Magazineâ€ is the requirement to accomplish the Bachelor Degree in English Linguistic at Faculty of Humanities, Sam Ratulangi University. This research aims at identifying, classifying and analyzing the kinds and internal functions of adverbial phrase which found in National Geographic Magazine.Â Â Â Â Â Â Â Â Â Â Â The theory that is used in this research by Aarts and Aarts (1982). Moreover, the method used in this study is descriptive method. The data of analysis of adverbial phrases is taken from the sentences in the article entitled Gilles de Rais: Making a Murderer of National Geographic Magazine edition November 2017.Â Â Â Â Â Â Â Â Â Â Â The results of this research show that from 56 kinds of adverbial, adverb of place (11 data), adverb of time (9 data), intensifying adverb and adverbs of degree (19 data), conjuncts (3 data), other adverbs (7 data), premodifier in the adjective phrase and adverbial phrase (2 data), premodifier in a noun phrase (1 data), postmodifier in a noun phrase (3 data), adverb premodify by preposition (1 data), and from internal functions there are 4 data such as premodifiers (3 data), postmodifier (1 data).Keywords:Â Analysis, Adverbial phrases, National Geographic, Magazine